Pyrolysis of rice straw; The effect of pyrolysis temperature and heating rate on the product yields - Razi, Ahmad; Khairuddin, Md Isa; Khairul Nizar, Ismail; Khudzir, Ismail; Maung Maung Soe (Universiti Kebangsaan Malaysia (UKM), 2011)
Regional Engineering Postgraduate Conference 2009 (EPC 2009) organized by Faculty of Engineering & Built Environment, Universiti Kebangsaan Malaysia, from 20th - 21st October 2009 at Palm Garden Hotel, Putrajaya, Malaysia.